Demonizing the Aggressors: Russian Icons of The Battle of Novgorodians against Suzdalians - Antonov, Dmitriy (IKON, 2022)
Abstract This paper discusses the role of details and minor figures in Russian medieval iconography. Studying an icon of The Battle of Novgorodians against Suzdalians, painted in the middle of the 15th century, the author reveals small visual elements that helped the artist(s) to blame and demonize the aggressors of the distant past. Combining details, the icon-painter enriched the image with many important nuances. However, tiny visual elements were hardly noticeable and clear to the viewers. The author analyses absurd figures that appeared in different icons as the result of the painters’ mistakes (the pagans with halos, the black angel) to ensure that little details normally remained unnoticed by parishioners and priests. This leads to the more general question about the possible recipient of the visual ‘micro-text’ and the role of details for the icon-painters. Abstract Demoniziranje agresora: ruske ikone Bitke između Novgorodaca i Suzdaljaca Rad je usmjeren na analizu uloge detalja i sporednih likova u ruskoj srednjovjekovnoj ikonografiji. Proučavajući ikonu Bitka između Novgorodaca i Suzdaljaca, nastalu sredinom 15. stoljeća, autor otkriva sitne likovne elemente koji su pomogli umjetnicima da okrive i demoniziraju agresore davne prošlosti. Kombinirajući detalje, koji su bili jedva uočljivi i razumljivi gledateljima, ikonopisac je sliku obogatio mnogim važnim nijansama značenja. Autor analizira besmislice koje se pojavljuju na različitim ikonama kao rezultat pogrešaka slikara (pogani s aureolama, crni anđeo) te pokazuje kako su ti sitni detalji obično ostali neprimjećeni od strane župljana i svećenika. To dovodi do općenitijeg pitanja o mogućem adresatu vizualnog “mikroteksta” i ulozi detalja za ikonopisce.